The Development of Intercultural Communicative Competence in Foreign Language Teaching - Bousba, Meriem (Journal of Human Sciences, 2016)
We make part of a contemporary globalized world characterized by extensive communication between people of different cultural backgrounds and languages. In a modern foreign language teaching and learning context, this entails that learners should be aided in developing their intercultural communicative competence. Put differently, in order to function appropriately and smoothly in intercultural situations, learners should be made aware of a set of fundamental facts about the culture that vehicles a foreign language, master a range of communicative skills and adopt new attitudes of tolerance and acceptance of culture-specific norms and behaviours. The present paper attempts to shed light on the situation of teaching culture at the Department of English, University of Jijel, and the need to develop third-year-LMD-students’ intercultural communicative competence